S100B Blood Level Determination for Early Management of Ski-Related Mild Traumatic Brain Injury: A Pilot Study - Kahouadji, Samy; Salamin, Pauline; Praz, Laurent; Coiffier, Julien; Frochaux, Vincent; Durif, Julie; Pereira, Bruno; Arlettaz, Lionel; Oris, Charlotte; Sapin, Vincent; Bouvier, Damien (Frontiers in Neurology, 2020)
Background: Mild traumatic brain injury (mTBI) management in emergency departments is a complex process involving clinical evaluation, laboratory testing, and computerized tomography (CT) scanning. Protein S100B has proven to be a useful blood biomarker for early evaluation of mTBI, as it reduces the required CT scans by one-third. However, to date, the ability of S100B to identify positive pathological findings in the CT scans of patients suffering from mTBI caused by ski practice has not been investigated. Thus, the primary aim of this study was to investigate the diagnostic performance of S100B as an mTBI management biomarker in patients with ski-related mTBI. Materials and Methods: One hundred and thirty adult mTBI patients presenting to the emergency department of Hôpital du Valais in Sion, Switzerland, with a Glasgow Coma Scale (GCS) score of 13–15 and clinical indication for a CT scan were included in the study. Blood samples for S100B measurement were collected from each patient and frozen in three-hour post-injury intervals. CT scans were performed for all patients. Later, serum S100B levels were compared to CT scan findings in order to evaluate the biomarker’s performance. Results: Of the 130 included cases of mTBI, 87 (70%) were related to ski practice. At the internationally established threshold of 0.1 µg/L, the receiver operating characteristic curve of S100B serum levels for prediction of pathologic CT scans showed 97% sensitivity, 11% specificity, and a 92% negative predictive value. Median S100B concentrations did not differ according to sex, age, or GCS score. Additionally, there was no significant difference between skiers and non-skiers. However, a statistically significant difference was found when comparing the median S100B concentrations of patients who suffered fractures or had polytrauma and those who did not suffer fractures. Conclusion: The performance of S100B in post-mTBI brain lesion screenings seems to be affected by peripheral lesions and/or ski practice. The lack of neurospecificity of the biomarker in this context does not allow unnecessary CT scans to be reduced by one-third as expected.